ANALYZING THE ADVANTAGES, CHALLENGES, AND PEDAGOGICAL IMPLICATIONS OF E-BOOKS IN ELEMENTARY ENGLISH LEARNING: A LITERATURE REVIEW - Saputri, Tiara Dwi; Misrita, Misrita; Putri, Librina Tria (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2024)
This study analyzes the advantages, challenges, and pedagogical implications of using e-books to enhance English language learning among elementary school students. As technology advances and becomes increasingly integrated into education, e-books have emerged as interactive resources that combine text, images, audio, video, and animations to support vocabulary development, reading comprehension, and student motivation. This literature review synthesizes findings from academic journal articles published between 2019 and 2024, focusing on how e-books contribute to effective English instruction in elementary contexts. The results indicate that e-books offer adaptive learning experiences tailored to diverse learning styles, significantly enhancing students’ engagement and language acquisition. Additionally, the review identifies challenges such as screen fatigue and digital inequality, which must be addressed to ensure equitable access and sustainability. Pedagogically, e-books encourage multimodal and constructivist learning, supporting individualized and collaborative classroom experiences. The findings highlight the importance of strategic implementation and teacher preparedness in maximizing the benefits of digital tools. This study aims to serve as a valuable reference for the design and development of innovative and inclusive e-book-based learning in elementary English education.